Seroprevalence of hepatitis B and C viruses in the province of Tokat in the Black Sea region of Turkey: A population-based study - Beytullah YILDIRIM; Şener BARUT; Yunus BULUT; Gülgün YENİŞEHİRLİ; Metin ÖZDEMİR; İlhan ÇETİN; Ali AKBAŞ; Ömer ATIŞ; Hüseyin ÖZYURT; Şemsettin ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-